Production of zinc iron phosphate glasses by microwave and conventional processing methods - Mohd Farhadi, Nur Hazeeqah (2020)
This thesis describes the production of zinc iron phosphate glasses, xZnO-(40- x)Fe2O3-60P2O5 with x = 0, 2.5, 5.0, 7.5, 10.0 (mol%) using microwave and conventional processing methods. The work aiming to investigate the potential use of microwave processing method for the production of zinc iron phosphate glasses. In microwave glass melting, magnetite powder coupled with microwave radiation within 10 minutes radiation time. Equivalent samples are conventionally prepared by melting the identical batches at 1300 ˚C for 3 hours in electric furnace. The mass loss trends for all samples are increased with the increasing of ZnO and in agreement with the theoretical data calculated from batch compositions. It is found that the mass loss of microwave samples increased about 2 % compared to conventionally made samples and this is due to the contribution of Fe2+ ion. XRD patterns confirmed the amorphous structure and revealed an identical diffuse scattering behaviour of all samples. The homogeneity of chemical compositions are evident from SEM images and the chemical analysis using EDS implied that the percentage amount of Zn, Fe and P in each of the glasses prepared using microwave method decrease compared to the samples formed using conventional method. The Tg data are in range of 459 – 476 ˚C and these agree with the mass loss and EDS analyses. Although the chemical properties of conventionally prepared samples are superior compared to the microwaved samples, the powder density analysis shown that the microwave samples possessed higher powder density values (3.0491, 3.0488 and 3.0343 g/cm3 ) at lower ZnO content (< 5 %). All in all, it is clear from the data that the microwave glass melting are promising and viable method as it retains high density of materials, rapid glass melting and reduce energy consumption compared to conventional glass melting.